Students' Perceptıons Of How To Teach Economıcs Teachers At Senior High School Muhammadıyah 1 Palangka Raya - Amalia, Sovia; Nurbudiyani, Iin; Sonedi, Sonedi; Jailani, Muhammad; Setiawan, Muhammad Andi (International Journal of Universal Education, 2023)
This study aims to determine students' perceptions of how to teach economics teachers at Senior High School Muhammadiyah I Palangkaraya. This study uses data collection techniques of observation, interviews, and documentation. Interviews were conducted with 10 students of class X IPS-2 regarding how to teach economics teachers. Observations and documentation were carried out on matters relating to students' perceptions of how to teach economics teachers at Senior High School Muhammadiyah 1 Palangkaraya. Descriptive research method with data collection techniques of observation, interviews, and documentation. This research was conducted from April to June 2022, located at Senior High School Muhammadiyah 1 Palangkaraya with the research subjects of 10 students consisting of teachers of economics subjects and students. Descriptive research method with data collection techniques of observation, interviews, documentation and questionnaires. This research was conducted from April to June 2022, located at Senior High School Muhammadiyah 1 Palangkaraya with the research subjects of 10 students consisting of teachers of economics subjects and students